Influence of alternative fuels on the particulate matter micro and nano-structures, volatility and oxidation reactivity in a compression ignition engine. (October 2020) - Mao, Dongxu; Ghadikolaei, Meisam Ahmadi; Cheung, Chun Shun; Shen, Zhaojie; Cui, Wenzheng; Wong, Pak Kin
Abstract: The present study investigates the impact of various alternative fuels, including biodiesel, methanol, ethanol, butanol and pentanol, on the micro and nano-structures, volatility and oxidation reactivity of particulate matter (PM) from a 4-cylinder compression ignition engine under low (10%) and high (80%) engine loads at a constant engine speed of 1800 rpm. Four alcohols were mixed with diesel and biodiesel to obtain ternary fuels. The overall oxygen concentration of each ternary fuel was fixed at 6% by mass for establishing the same condition for comparing. In addition to the ternary fuels, pure biodiesel was also compared with diesel fuel. The results of the micro and nano-structures characteristics obtained from a Scanning Transmission Electron Microscope (STEM) reveal that the alternative fuels can disorder the PM micro and nano-structures, and also the particles produced by these fuels have lower primary particle diameter, particle agglomerate size and fringe length, however, higher fringe tortuosity and almost equal (insignificant rise) fringe separation distance compared to those produced by diesel fuel. The results obtained from a Thermogravimetric Analyzer/Differential Scanning Calorimeter (TGA/DSC) show that both biodiesel and alcohols have the potential to increase in PM volatile substances and oxidation reactivity rate, and decrease in PM non-volatile substances in comparison with those of diesel fuel. It is concluded that the pure biodiesel has the highest impact on the PM structure, volatility and oxidation reactivity among all the tested alternative fuels, while methanol has the highest impact on these parameters among all the tested alcohol fuels. Highlights: PM structure, volatility and oxidation reactivity of diesel engine were analyzed. Diesel, biodiesel, methanol, ethanol, butanol and pentanol fuels were tested. Biodiesel has the highest PM volatility, oxidation reactivity and fringe tortuosity. Biodiesel has the lowest non-volatile substances, particle size and fringe length. After biodiesel, methanol blend has the highest effect on the PM parameters.